Marketing Efficiency of The â€œEmping melinjoâ€ in Farmer Women Groups in Batang Region, Central Java - Kusnaman, Djeimy; Sunendar, Sunendar; Sukmaya, Syahrul Ganda (Master of Management Diponegoro University, 2021)
This study aims to examine the marketing efficiency of processed melinjo in women's farmer groups with data collected in Batang Regency, Central Java. Emping melinjo has contributed to providing additional work for mothers as a side business. The method used in this research is a survey of KWT Tani Rejo. Melinjo emping producer data was collected by purposive (deliberate) and traders' samples were done by snowball sampling and respondents were taken by census on all members of KWT Tani Rejo. The data obtained were analyzed descriptively and calculated using margin analysis and farmer share. The results show that the first channel of emping melinjo marketing is the most efficient than the second and third channels. Producers accept higher prices and do not bear marketing costs, because they sell directly to consumers. Meanwhile, marketing efficiency on channels 2 and 3 is greater than 30%. Margins on channels 2 and 3 reached 40% and 16% respectively. Marketing actors include producers, collectors, wholesalers, agents, and retailers. The involvement of women in this business group is due to limited costs and access to market information.